2019
DOI: 10.1111/head.13601
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Heart of the Matter: Migraine, Triptans, DHE, Ditans, CGRP Antibodies, First/Second‐Generation Gepants, and Cardiovascular Risk

Abstract: Premise The science of migraine pathophysiology has advanced significantly since the 1930’s. Imaging techniques, neurochemical analysis, clinical trials, and the clinical experience of providers treating migraine patients have not only sharpened our understanding of the disease, but have also led to the development of novel neural‐based targets. Targeted therapies such as calcitonin gene‐related peptide (CGRP) antibodies and “Second Generation” CGRP receptor antagonists (Gepants) have not only demonstrated eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The PK data confirmed the high C max seen with IV administration (58,321 pg/mL) compared to the C max with MAP0004 (2475 pg/mL after first dose and 3063 pg/mL after second dose) that was effective in the clinical studies. 27,76 A recent review examined the evidence of cardiovascular safety concerns with DHE (and triptans) and suggested that evidence for harm with these 5HT agonists is missing 81 even for those suffering from what is now classified as Migraine with Brainstem Aura (MBA) or Hemiplegic Migraine. 82 The final concluding statement from the review reminded us of the primary role of neuronal processes in the pathophysiology of migraine, rather than vascular.…”
Section: Dhe -Cardiac Safetymentioning
confidence: 99%
“…The PK data confirmed the high C max seen with IV administration (58,321 pg/mL) compared to the C max with MAP0004 (2475 pg/mL after first dose and 3063 pg/mL after second dose) that was effective in the clinical studies. 27,76 A recent review examined the evidence of cardiovascular safety concerns with DHE (and triptans) and suggested that evidence for harm with these 5HT agonists is missing 81 even for those suffering from what is now classified as Migraine with Brainstem Aura (MBA) or Hemiplegic Migraine. 82 The final concluding statement from the review reminded us of the primary role of neuronal processes in the pathophysiology of migraine, rather than vascular.…”
Section: Dhe -Cardiac Safetymentioning
confidence: 99%
“…According to SHAP analysis, the most relevant features in the DeepLORI model for migraine relate to the prior existence of headaches and the use of drugs for the nervous system, which are typically used to treat headaches. In addition, many drugs used for treating headaches are known to affect the liver (Mathew and Klein, 2019;Valade, 2019). It is known that females are more affected by migraine than males, and that migraine is age-dependent (Victor et al, 2010).…”
Section: Deeplori Models Are Explainablementioning
confidence: 99%
“…Diseases such as hemiplegic migraine or migraine with complicated aura also do not allow the intake of a triptan. 5 Among the risk factors for cardiovascular disease, obesity is on the rise, also affecting a younger population. 6 Together with other risk factors; for example, hypercholesterinemia or diabetes, these changes in the general population may also lead to significantly more migraine patients with cardiovascular disease, who are in need for acute antimigraine drugs without vasoactive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases such as hemiplegic migraine or migraine with complicated aura also do not allow the intake of a triptan. 5…”
Section: Introductionmentioning
confidence: 99%